Exploitation of Nanobifiller in Polymer/Graphene Oxide–Carbon Nanotube, Polymer/Graphene Oxide–Nanodiamond, and Polymer/Graphene Oxide–Montmorillonite Composite: A Review. (2nd May 2016) - Khan, Dost Muhammad; Kausar, Ayesha; Salman, Syed M.
ABSTRACT: In this article, a comprehensive review is presented regarding structure, synthesis, and properties of nanofillers such as graphene oxide, nanobifiller of graphene oxide, and their polymeric nanocomposite. The information about hybrid properties and synthesis of graphene oxide–carbon nanotube, graphene oxide–montmorillonite, and graphene oxide–nanodiamond is presented. Use of nanobifiller in polymer/graphene oxide–carbon nanotube, polymer/graphene oxide–montmorillonite, and polymer/graphene oxide–nanodiamond composites was summarized. Area of polymer and graphene oxide-based nanobifiller composites is less studied in literature. Therefore, nanobifiller technology limitations and research challenges must be focused. Polymer/graphene oxide nanobifiller composites have a wide range of unexplored potential in technological areas such as automobile, aerospace, energy, and medical industries. GRAPHICAL ABSTRACT: